2019
DOI: 10.3389/fnins.2019.00491
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and Autophagy in Neurodegeneration

Abstract: Crosstalk in the pathophysiological processes underpinning metabolic diseases and neurodegenerative disorders have been the subject of extensive investigation, in which insulin signaling and autophagy impairment demonstrate to be a common factor in both conditions. Although it is still somewhat conflicting, pharmacological and genetic strategies that regulate these pathways may be a promising approach for aggregate protein clearancing and consequently the delaying of onset or progression of the disease. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 177 publications
0
38
0
Order By: Relevance
“…This primordial membrane is called phagophore, which will, in a second step, fuse at its edges forming a double-membrane vesicle called autophagosome. The autophagosomes will undergo a maturation step in which they fuse with acidified lysosomal or endosomal vesicles to finally degrade a damaged element and recycle it ( Figure 3A) (160,161).…”
Section: Autophagy In Aged Brainmentioning
confidence: 99%
“…This primordial membrane is called phagophore, which will, in a second step, fuse at its edges forming a double-membrane vesicle called autophagosome. The autophagosomes will undergo a maturation step in which they fuse with acidified lysosomal or endosomal vesicles to finally degrade a damaged element and recycle it ( Figure 3A) (160,161).…”
Section: Autophagy In Aged Brainmentioning
confidence: 99%
“…Further, we performed the knowledge-based ingenuity pathway analysis (IPA) tool to identify the common pathways which could be dysregulated in the brain. We found that sirtuin signalling pathway 63 , cardiac hypertrophy signalling, estrogen receptor signalling, insulin secretion signalling 64 and signalling by Rho Family GTPases were upregulated in DJ-1 −/− mice while hepatic fibrosis signaling pathway, endothelin-1 signalling, ephrin receptor signalling, fMLP signalling in neutrophils were down regulated based on Z-score ( Fig. 6c).…”
Section: Increased Inflammatory Genes Related To Pd In Dj-1 −/− Mice mentioning
confidence: 86%
“…This in turn was associated with an increased mTORC phosphorylation at the Akt sensitive site, Ser2448 (43). Multiple lines of evidence implicate the activation of the insulin receptor/Akt/mTORC signaling pathway in suppression of autophagy associated with insulin resistance in neurons (67) and peripheral tissue (68). mTORC activation represses the activity of the unc-51-like kinase 1 (ULK1) via phosphorylation, and thus precludes autophagosome maturation (69).…”
Section: Discussionmentioning
confidence: 99%